ИССЛЕДОВАНИЯ ВЛИЯНИЯ ТЕРМИЧЕСКИХ ОБРАБОТОК НА ПОКАЗАТЕЛИ КАЧЕСТВА ИГРИСТЫХ ВИН - Татьяна Александровна Дроздова; Наталья Михайловна Агеева; Максим Витальевич Поспелов (Ползуновский вестник)
The article is devoted to a study aimed at identifying and developing technological techniques that ensure the intensification of enzymatic reactions in yeast biomass during the post-aging of sparkling wine and, as a result, a significant reduction in the aging time and improvement of the quality of the finished product. In order to study the mechanism of autolysis of yeast during the period of post-run exposure, the effects of temperature regimes of circulation treatments on changes in its physico-chemical and biochemical parameters in conditions excluding increased pressure and tightness of the medium were investigated. For this purpose, starting from the initial wine material and, operationally, in the circulation model, the activity of oxidative and hydrolytic enzymes was analyzed, the content of protein and amine nitrogen, as well as the foaming ability were determined.